2019
DOI: 10.1055/s-0039-3399519
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Cerebrospinal Fluid Leaks of the Anterior Skull Base: Algorithm for Diagnosis and Management

Abstract: Objective Pseudo-cerebrospinal fluid (CSF) leaks are a rare cause of unilateral, watery rhinorrhea. We proposed a step-wise approach to evaluate these cases. Design It involves a single-center retrospective cohort study. Setting The setting is that of a tertiary academic medical center. Participants Ten patients with diagnosis of pseudo-CSF leak over a 21-year period were evaluated using our proposed algorithm that includes computed tomography, magnetic resonance imaging, nasal en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…3 Constanzo et al described 40% of cases of posttraumatic rhinorrhea. 6 Our study found 23 cases, or 17.3%, of posttraumatic rhinorrhea. The frequency of rhinorrhea during a fracture of the anterior skull base in our study is lower than in the literature.…”
Section: Discussionmentioning
confidence: 45%
“…3 Constanzo et al described 40% of cases of posttraumatic rhinorrhea. 6 Our study found 23 cases, or 17.3%, of posttraumatic rhinorrhea. The frequency of rhinorrhea during a fracture of the anterior skull base in our study is lower than in the literature.…”
Section: Discussionmentioning
confidence: 45%
“…UCTR in these scenarios has been presumed to be due to a hyperactive or unopposed parasympathetic state. Reinforcing this notion, some of the patients in these series reported rhinorrhea reduction after initiating IBNS 21,22,24,25 …”
Section: Discussionmentioning
confidence: 52%
“…There have been multiple reports of UCTR being caused by non-CSF conditions, including rhinitis, 21,22 cervical sympathetic chain surgery, 23 post-procedural rhinorrhea after sedation and supplemental oxygen use, 24 head trauma or skull base fractures, 21,22,25 anterior and lateral skull base surgeries, 12,21,22,26 and other sinonasal surgeries as well. 22 UCTR in these scenarios has been presumed to be due to a hyperactive or unopposed parasympathetic state. Reinforcing this notion, some of the patients in these series reported rhinorrhea reduction after initiating IBNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of postoperative CSF leak was based on clinical examination, imaging, and laboratory testing, following a standardized protocol. 21 Diagnosis of intracranial infection was based on clinical examination, CSF analysis, and CSF culture. A negative CSF culture did not rule out infection if clinical signs were present with a compatible CSF analysis.…”
Section: Methodsmentioning
confidence: 99%